Reporting errors, incidence and risk factors for postpartum haemorrhage and progression to severe PPH: a prospective observational study. (12th February 2014) - Briley, A; Seed, PT; Tydeman, G; Ballard, H; Waterstone, M; Sandall, J; Poston, L; Tribe, RM; Bewley, S
<x xml:space="preserve">Abstract</x> Objective To quantify reporting errors, measure incidence of postpartum haemorrhage (PPH) and define risk factors for PPH (≥500 ml) and progression to severe PPH (≥1500 ml). Design Prospective observational study. Setting Two UK maternity services. Population Women giving birth between 1 August 2008 and 31 July 2009 (n = 10 213). Methods Weighted sampling with sequential adjustment by multivariate analysis. Main outcome measures Incidence and risk factors for PPH and progression to severe PPH. Results Errors in transcribing blood volume were frequent (14%) with evidence of threshold preference and avoidance. The incidences of PPH ≥500, ≥1500 and ≥2500 ml were 33.7% (95% CI 31.2–36.2), 3.9% (95% CI 3.3–4.6) and 0.8% (95% CI 0.6–1.0). New independent risk factors predicting PPH ≥ 500 ml included Black African ethnicity (adjusted odds ratio [aOR] 1.77, 95% CI 1.31–2.39) and assisted conception (aOR 2.93, 95% CI 1.30–6.59). Modelling demonstrated how prepregnancy‐ and pregnancy‐acquired factors may be mediated through intrapartum events, including caesarean section, elective (aOR 24.4, 95% CI 5.53–108.00) or emergency (aOR 40.5, 95% CI 16.30–101.00), and retained placenta (aOR 21.3, 95% CI 8.31–54.7). New risk factors were identified for progression to severe PPH, including index of multiple deprivation (education, skills and training) (aOR 1.75, 95% CI 1.11–2.74), multiparity without caesarean section (aOR 1.65, 95% CI 1.20–2.28) and administration of steroids for fetal reasons (aOR 2.00, 95% CI 1.24–3.22). Conclusions Sequential, interacting, traditional and new risk factors explain the highest rates of PPH and severe PPH reported to date.